Politics and constitutions in Southeast Asia - Bunte, Marco; Dressel, Bjorn (Routledge law in Asia series ;, 2017)
In recent years the constitutional landscape of Southeast Asia has changed tremendously. This book explores a range of current constitutional developments in the different states of Southeast Asia through a distinct political lens. The book concludes by assessing overall how far constitutional practices and trajectories are converging towards a liberal Western model or towards a distinctly Southeast Asian model.